Pengaruh Employee Engagement dan Budaya Organisasi Terhadap Kinerja Karyawan pada Yayasan Pendidikan Avicenna Prestasi - Gita Aulia Darma Putri (Pusat Riset dan Inovasi Nasional, 2025)
Strong organizational culture and engaged employees will improve performance which has a very positive effect on the sustainability of an organization. This study aims to analyze the impact of employee engagement and organizational culture on employee performance at the Avicenna Prestasi Education Foundation. The research method used is a quantitative method with a descriptive approach. The data was collected through a questionnaire distributed to 50 respondents selected using the Slovin method. The results showed that employee engagement and organizational culture significantly have a positive effect on employee performance. This means that maintaining and improving employee engagement and organizational culture can improve employee performance at the Avicenna Prestasi Education Foundation. This study contributes to the understanding of human resource management in companies and can be the basis for policies to improve employee performance and satisfaction.